Institutional factors and job satisfaction of the nursing professional of the Hospital María Auxiliadora, Lima. - Huamán Salazar, Nancy (2019)
Objetive: This study determines the relationship between institutional factors and job satisfaction of the nursingprofessional at Maria Auxiliadora Hospital. Material and Methods: It is a quantitative research approach, nonexperimental, correlational and cross-sectional descriptive. The sample consisted of 130 nurses working in thevarious departments of Maria Auxiliadora Hospital. The data collection technique was survey and the instrumenta questionnaire prepared by the researcher. Results: The results show that 93.1% of the sample are female and6.9% males. Age percentages are 43% over 40 years old, 22.3% between 35 and 40 years and 34.7% are under35. Regarding marital status, 44.6% are married and 42.3% single. In respect to time of service in the institution,34.6% have worked less than 5 years, 32.3% 5 to 14 years and 33.1% over 15 years. There is a direct andsignificant relationship between institutional factors and job satisfaction (Rho = 0.272, p = 0.002). It was alsofound that institutional factors wage (Rho = 0.378, p = 0.000), working conditions (Rho = 0.227, p = 0.009) andadministrative policies (Rho = 0.234, p = 0.007) have a direct and significant relationship with work satisfaction.However, supervising factors (Rho = 0.059, p = 0.502) and interpersonal relationships (Rho = -0,012, p = 0.888)have no statistical evidence regarding job satisfaction. Ratio analysis was through the Spearman's rank correlationcoefficient. Conclusions: Direct and significant relationship of wages, working conditions and administrativepolicies, represent satisfaction; not, supervision and interpersonal relationships, which prevent dissatisfaction.